A non-interactive certificateless two-party authenticated key agreement protocol for wireless sensor networks. (2016) - Bala, Suman; Verma, Anil K.
Key agreement protocol(s) is one of the important factors for establishing communication between two parties. Recent works support the use of pairing free certificateless authenticated key agreement protocol(s) and becomes a promising base in a energy-famished WSN. Certificateless concept provides an authentication by eliminating the need of certificates of traditional public key cryptography and key escrow problem of identity based cryptography (IBC). This paper presents a non-interactive Certificateless two-party authenticated key agreement (NI-CTAKA) protocol for WSN. NI-CTAKA is pairing-free as well as reduces number of scalar point multiplications. NI-CTAKA has been implemented on MICAz platform using TinyOS-2.1.2 and RELIC-0.3.3 cryptographic library and the results has been analysed for storage-cost, running time and energy consumption. Further, NI-CTAKA is proven to be secure in the security model presented by Lipold et al. extended Canetti-Krawczyk (eCK) model. The comparative analysis proves that the proposed protocol is more efficient than the existing protocols.